Strategi Human Relations Dalam Mewujudkan Zero Accident - Wulansari, Rapi; Rizki, Annisa; Pitasari, Dwi Nurina (CommLine, 2023)
This study was conducted to determine the Human Relations Strategy in Realizing Zero Accident (Case Study on HRD PT. Grand Pintalan Textile) by analyzing the strategy using the POAC strategy (Planning, Organizing, Actuating, Controlling). The research uses organizational control theory. The selection of informants was done by the purposive sampling method. Research data was obtained by data collection techniques with in-depth interviews, participant observation, and documentation. This research uses the post-positivism paradigm, a qualitative approach with a case study method. The big concept used is the POAC management concept from G.R Terry. The results of this study show that the HRD Strategy of PT. Grand Pintalan Textile to achieve zero accidents is carried out with four strategies consisting of simple, technical, bureaucratic, and conservative supervision. Besides that, PT. Grand Pintalan Textile implements the POAC strategy through the Human Relations Department. This POAC strategy can be seen from the activities carried out by the Human Relations Department which include knowledge of what to do (planning), determining how to do it (organizing), understanding how they should do it (actuating), and measuring the effectiveness of the efforts that have been made. (controlling).